Analisis Rantai Pemasaran Produk Industri Meubel PD. Tabulik - Imlabla, Wilma N.; Limba, Samuel; Sahureka, Mersiana; Keliwouw, Makbul A. (Universitas Pattimura, 2019)
The PD. Tabulik furniture industry is one of the furniture industries that is believed to be superior in global competition. Therefore, strategic policies related to the optimal marketing chain are needed in maintaining business sustainability amid market competition. Consequently, the research aims to analyze the marketing chain of furniture industry products. The research method uses survey methods and in-depth interviews with all marketing channel components and the marketing chain analysis of the research object's outcome. The results show that the marketing chain is used by PD. Tabulik is a short marketing channel model that is direct producers to end consumers and is still limited in the Maluku region. The products' marketing chain gets shorter and shorter, so the final consumer is not charged with the purchase cost. But PD.Tabulik needs to fix the marketing chain management and marketing mix efficiently and optimally.